Distributed outreach for literacy and access: Efforts to bridge accessibility, availability, and awareness of quality education for underprivileged groups to support local empowering and community development - Khairunnisa, Pratiwi; Hanif, Fairuzzidan Fadhil; Prasetyo, Charly (Institute for Advanced Science Social, and Sustainable Future, 2025)
Background: Unequal access to quality education for underprivileged groups in Indonesia remains a critical issue, perpetuating cycles of poverty. Marginalized groups face significant challenges, including stigma, economic and geographic disparities, which hinder their access to education and literacy. Method: This study employs a qualitative approach, using secondary data from journals, articles, and existing surveys to explore the challenges marginalized groups face in accessing education. Findings: The analysis reveals that while economic and geographic barriers are prominent, a lack of government focus on local empowerment exacerbates the problem. The existing approaches do not sufficiently address the root causes or involve marginalized communities in meaningful ways. Conclusion: The study suggests that a more inclusive approach is needed, such as the DORA (Distributed Outreach for liteRacy and Access) program. DORA aims to promote widely distributed education, enhance literacy awareness, and foster local empowerment and development within marginalized communities. Novelty/Originality of this Study: This study introduces the DORA program as an innovative solution to the persistent educational challenges faced by marginalized groups. By emphasizing local empowerment and widespread literacy efforts, it offers a fresh perspective on addressing educational inequality in Indonesia.